Infrastructure in Industrial Development (Food and Beverages) in North Maluku Province - Daud, Nahu; Zamzam, Irfan; Rasulu, Hamidin (Agrikan Jurnal Agribisnis Perikanan, 2022)
Infrastructure development in an area is one of the keys to economic growth. Furthermore, infrastructure facilities can encourage growth in the labor sector will grow productively and are supported by business capital that can reduce production costs, increase operating profits, the amount of production will continue to increase, and be able to improve community welfare. But on the contrary, with limited infrastructure facilities, it causes the value of productivity to decrease. The purpose of this study is to provide an overview of regional conditions and infrastructure developments in the development of industry (food and beverages) in North Maluku Province. This study uses the descriptive analysis method to see the extent of infrastructure conditions in supporting regional industrial development to facilitate industrial activities in this area. Based on the results of the study, all physical infrastructure in the form of roads, ports, airports, clean water, telecommunications, and electrical energy that is already available in North Maluku Province will contribute to industrial development in North Maluku. However, to support the development of the industrial sector in this area which has enormous potential, the infrastructure currently owned has become very limited and is felt to be unable to support the needs of the industrial sector. So that to catch up with the carrying capacity of infrastructure for the industrial sector, it must have policies for the development and development of this infrastructure. In conclusion that necessary to coordinate between provincial, district and city governments in determining development priorities in North Maluku Province.